T‐cell response to phytohemagglutinin in the interferon‐γ release assay as a potential biomarker for the response to immune checkpoint inhibitors in patients with non‐small cell lung cancer. Issue 11 (4th May 2021) - Kamimaki, Chisato; Kobayashi, Nobuaki; Hirata, Momo; Somekawa, Kohei; Fukuda, Nobuhiko; Kubo, Sousuke; Katakura, Seigo; Teranishi, Shuhei; Watanabe, Keisuke; Horita, Nobuyuki; Hara, Yu; Yamamoto, Masaki; et al.
Abstract: Background: Immune checkpoint inhibitors are a standard treatment for advanced lung cancer, although it remains important to identify biomarkers that can accurately predict treatment response. Immune checkpoint inhibitors enhance the antitumor T‐cell response, and interferon‐γ plays an important role in this process. Therefore, this study evaluated whether the number of interferon‐γ‐releasing peripheral T cells after phytohemagglutinin stimulation in the interferon‐γ release assay might act as a biomarker for the response of non‐small cell lung cancer to immune checkpoint inhibitor treatment. Methods: Data were retrospectively collected regarding 74 patients with non‐small cell lung cancer who had received immune checkpoint inhibitors. Pretreatment screening tests had been performed using the T‐SPOT.TB assay, which quantifies the number of interferon‐γ‐releasing T cells (as immunospots) in response to phytohemagglutinin and tuberculosis‐specific antigen stimulation. Clinical factors and the number of spots in the T‐SPOT fields were evaluated for associations with patient outcomes. The median number of spots was used to categorize patients as having high or low values, and the two groups were compared. Results: Relative to patients with a low ratio, patients with a high ratio of phytohemagglutinin/tuberculosis‐specific antigen spots (i.e. more responsive T cells) had significantly better progression‐free survival after immune checkpoint inhibitor treatment. When we only considered patients with negative T‐SPOT results, a high number of phytohemagglutinin‐stimulated spots corresponded to significantly longer progression‐free survival. Conclusion: The T‐SPOT.TB assay can be used to quantify the number of immunospots in response to antigen stimulation, which may predict the response to immune checkpoint inhibitors in patients with non‐small cell lung cancer. Abstract : This study evaluated whether the T‐SPOT test could be used to predict the response to immune checkpoint inhibitor treatment in patients with non‐small cell lung cancer. Among patients with negative T‐SPOT results, a high number of phytohemagglutinin‐stimulated spots was associated with longer progression‐free survival.